Publishing policies in open access journals: A literature review - Alnasser, Fahad Saad (Journal of Humanities & Social Sciences, 2023)
This paper aims to review the literature of publishing policies in open access journals. This paper relied on both the Arabic and English intellectual production, with the expansion of English intellectual production due to its abundance and progress in addressing the subject of the research. The simple approach (stand-alone) is used to present previous studies related to the research topic. The paper reviewed 67 scientific papers related to the subject of the research. The paper reviewed open access in its general form and its social and economic impact, then the beginning of the emergence of open access and the reasons for that. Then the research focused on publishing policies in open access journals, types of publication in these journals, classifications, publishing fees, arbitration, copyright, privacy, and the impact of open access on reference citations, then talking about the policies and labels of exploitative journals. The most important recommendations in this paper are the need for publishers to document publishing policies in open access journals, as well as paying attention to arbitration research in scientific journals and explaining the arbitration policy. In addition to that, the contribution of publishers to educating researchers and readers about the importance of publishing in open access journals, and the need to speed up arbitration processes in a way that serves science and does not affect the quality of research Scientific.